Effect of Employee, Salary And Cooperatives on Employee Satisfaction Main Rains Chicken Noodles and Medan Coffee - Ocdy Amelia (Institute of Computer Science (IOCS), 2021)
This research is the effect of work, salary and co-workers on employee job satisfaction at Sinar Utama Mie Ayam and Kopi Medan. Furthermore, the data obtained from the distribution of questionnaires or questionnaires from 35 respondents. The model used is Multiple Linear Regression and processed using SPSS version 20. The results of the analysis using the t test can be seen that one independent variable, namely work (X1) has a positive but not partially significant effect on the dependent variable, namely job satisfaction (Y) while it is known that two independent variables, namely salary (X2) and co-workers (X3) have a positive and partially significant effect on the dependent variable, namely job satisfaction (Y). Then the results of the analysis using the F test can be seen that the three independent variables, namely work (X1), salary (X2) and coworkers (X3) together have a positive and significant effect on the dependent variable, namely job satisfaction (Y). The results of the analysis using the coefficient of determination, it is known that 80.5% of job satisfaction can be obtained and explained by work, salary and co-workers. While the remaining 19.5% is explained by other variables not included in this study.